INTERACTIVE E-MODULE BASED ON THE WISDOM OF THE BADUY TRIBE TO IMPROVE NUMERACY IN STATISTICS MATERIALS - Wahdiani, Sri; Nindiasari, Hepsi; Hendrayana, Aan (EMTEKA: Jurnal Pendidikan Matematika, 2026)
This development research was motivated by students' low numeracy skills and the limited use of contextual teaching materials that integrate local wisdom in mathematics learning. This is evidenced by Indonesia's mathematics score in PISA 2022, which reached only 366, far below the OECD average of 472. Therefore, this study aimed to develop interactive e-modules based on the local wisdom of the Baduy tribe that are feasible, practical, and effective in improving students' numeracy skills in statistics. One of the contributing factors to low numeracy skills is the limited use of contextual and technology-based teaching materials, as well as learning approaches that have not fully emphasized Higher Order Thinking Skills (HOTS) and authentic problem-solving contexts. Therefore, integrating local wisdom and interactive digital media into teaching materials can be a relevant strategy to enhance students' numeracy skills. This study employed a Research and Development (R&D) approach using the ADDIE model. Data were collected through questionnaires and numeracy tests administered in the form of pretests and posttests based on AKM-type questions. Validation results from media, material, and education experts were all categorized as very feasible, while teacher and student responses were categorized as very practical. The effectiveness test using the N-gain score yielded 0.81, indicating high effectiveness. The integration of contextual cultural content, interactive features, and data visualization in the e-module can support students in understanding statistical concepts and solving real-world problems. Therefore, the developed product can serve as an alternative contextual digital learning resource to support numeracy-oriented mathematics learning in secondary schools. Penelitian pengembangan ini melatar belakangi pada rendahnya kemampuan numerasi peserta didik dan terbatasnya penggunaan bahan ajar kontekstual yang mengintegrasikan kearifan lokal dalam pembelajaran matematika. Hal ini dibuktikan dengan skor matematika Indonesia pada PISA 2022 yang hanya mencapai 366, jauh di bawah rata-rata OECD sebesar 472. Oleh karena itu, penelitian ini tujuannya untuk memberi pengembangan e-modul interaktif berbasis kearifan lokal suku Baduy yang layak, praktis, dan efektif dalam meningkatkan kemampuan numerasi peserta didik pada materi statistika. Suatu faktor penyebab rendahnya kemampuan numerasi adalah terbatasnya penggunaan bahan ajar kontekstual berbasis teknologi, serta pendekatan pembelajaran yang belum sepenuhnya menekankan pada Higher Order Thinking Skills (HOTS) dan konteks pemecahan masalah autentik. Oleh karena itu, pengintegrasian kearifan lokal dan media digital interaktif ke dalam bahan ajar dapat menjadi strategi yang relevan untuk meningkatkan kemampuan numerasi peserta didik. Penelitian ini memakai suatu pendekatan Research and Development (R&D) dengan model ADDIE. Data dikumpul kan pada angket dan tes numerasi yang diberikan dalam bentuk pretest dan posttest berbasis soal tipe AKM. Hasil validasi dari ahli media, ahli materi, dan ahli pendidikan seluruhnya berkategori sangat layak, sementara respons guru dan peserta didik berkategori sangat praktis. Uji efektivitas menggunakan skor N-gain menghasilkan nilai 0,81 yang termasuk dalam kriteria tinggi. Pengintegrasian konten budaya kontekstual, fitur interaktif, dan visualisasi data dalam e-modul dapat membantu peserta didik dalam memahami konsep statistika dan menyelesaikan masalah kehidupan nyata. Dengan demikian, produk yang dikembangkan dapat dijadikan alternatif sumber belajar digital kontekstual untuk mendukung pembelajaran matematika berorientasi numerasi di sekolah menengah..